P36 Consent for Orthopaedic Trauma Surgery during the COVID-19 Pandemic. (8th April 2021) - Walker, J; Davies, A; Heaton, T; Sabharwal, S; Fertleman, M; Dani, M; Reilly, P
Abstract: Surgical services have been hugely disrupted by COVID-19 and have had to evolve rapidly in response. The best practice for consent mandates that risks associated with surgical treatment during a pandemic be discussed. This study aimed to assess whether patients undergoing orthopaedic operations were being consented for the risk of contacting COVID-19 and ITU care. All orthopaedic consent forms from four-week periods in March, June and July were reviewed. Measures such as staff education were implemented after the second cycle. Of consent forms for 37 operations performed in March, only 1 mentioned the risk of contracting COVID-19 and zero mentioned ITU. During June, 89 consent forms were reviewed, 32 mentioned COVID-19 and 10 discussed ITU admission. Following educational measures, the third cycle showed a significant improvement as of 100 consent form records available for review, 73 included risk of COVID-19 whilst 26 mentioned ITU. The results show that earlier in the pandemic, surgeons at our centre were not counselling patients regarding COVID-19. This improved slightly between the first and second cycles, likely reflecting increased awareness of the nosocomial transmission of COVID-19. Educational measures contributed to a significant improvement in the third cycle. Planned interventions include use of electronic consent forms which incorporate COVID-19 infection and associated risks.